Filipino Health Care Aides and the Nursing Home Labour Market in Winnipeg - Novek, Sheila (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2013)
Canada’s nursing homes have become increasingly dependent on immigrant health care aides. More than any other ethnic group, Filipino women are over-represented among health care aides in the Canadian health care system. This qualitative study explored the employment experiences of Filipino health care aides in nursing homes from their own perspectives as well as those of policy stakeholders. Fourteen in-depth interviews were conducted with Filipino health care aides and long-term-care policy stakeholders in Winnipeg, Manitoba. The results indicated that migrant social networks act as pathways linking immigrant women with employment opportunities in nursing homes. The composition of the labour force is also shaped by management strategies and labour market accommodations that respond to, and reinforce, these social networks. These findings have implications for workforce planning and the quality of care provision in nursing homes.